The “Authorship Index” - a simple way to measure an author’s contribution to literature - Kaushik, Robin (International Journal of Research in Medical Sciences, 2017)
Writing scientific papers is an important part of ‘academic’ medicine, not only to present one’s experience and innovations, but also to assess a person’s contribution and impact on scientific Literature. In addition, publications also play a crucial role in assessing a person for jobs, promotions, or funding. In the light of these facts, then, it becomes important to have a good number of publications so that one’s CV becomes impressive. However, in this race to have large number of scientific publications, these facts also encourage the publication of papers with negligibly important scientific content and also the issues of gifted authorship, where a person who has not contributed significantly to the actual process of either conceptualising or writing the manuscript is acknowledged as an author for various local compulsions.